TARİHÇİLİĞİN BUNALIMI VE TARİH’İN DOĞUŞU-İbni Halduncu Çözümlemenin Özgünlüğü Üzerine- - Mehmet Evkuran (İslami İlimler Dergisi)
In both of Islamic tradition and modern western social sciences (espacially in history science) the name of Ibn Khaldun is one of the most recognized and esteemed scholar. His originality is based on his studies on the nature of history and structure of society. Ibn Khaldun believed that the historical and social events may comprehended by human mind and he made an effort to understand the logic of its events. He claimed that social events must been explained in the context of cause-result relations. To understand and explain the history departing from its own roots, considered the arising of history as a science in the modern scinetific meaning. Thus we look at his masterwork, Mokaddime, we can seee that concepts which used for defining the social and historical changes, are very concrete. In this article I try to show the originality of Ibn Khaldun’s thoughts on historical studies and to indicate his contributions to the idea of history in the scientific context.